Public transport planning and operations - Seminar on Public Transport Planning and Operations (1995 : Brunel University); Planning and Transport Research and Computation International Association; PTRC European Transport Forum (24th : 1996 : Brunel University) (London : PTRC Education and Research Service, 1996)
08